IMPLIKASI SHARIAH GOVERNANCE TERHADAP REPUTASI DAN KEPERCAYAAN BANK SYARIAH - Wardayati, Siti Maria (WALISONGO, 2011)
AbstractThe object of this study is Bank Muamalat Indonesia in Central Java, while thenumber of samples used was 200 respondents using purposive sampling techniques.The techniques of analysis used descriptive analysis and SEM analysis with the helpof AMOS. The results of computational data show that the implementation of shariagovernment that consists of 6 (six) indicators, namely: transparency, accountability,responsibility, indedendency, justice and shariah compliance has shown good results.Shariah compliance is an indicator of the dominant Islamic government, whileresponsibility and justice is an indicator of weak governance in explaining sharia.Implementation of shariah governance significant effect on the reputation andcustomer confidence in Islamic banks.